Clinical implications of first and multiple locoregional breast cancer recurrences - Wenners, Antonia; Berlin, Lena; Alkatout, Ibrahim; Van Mackelenbergh, Marion; Jonat, Walter; Mundhenke, Christoph (Archives of Gynecology and Obstetrics, 2015)
Purpose: Often breast cancer can be treated by breast-conserving surgery (BCS), after which 10 % locoregional recurrences (LRR) occur within 10 years. After BCS mastectomy is recommended at first LRR, although another BCS could be possible. Changes in clinical parameters and in tumor biology from primary breast cancer to first and multiple LRR are described and correlated with further LRR and overall survival (OS). Methods: 380 patients with ≥1 ≤3 LRR (1997–2007) were evaluated retrospectively and followed until 5/2009. Patients’ age, tumor size, nodal involvement, distant metastases, histological subtype, hormone receptor (HR) and Her-2/neu status were assessed. LRR therapy options were evaluated. Results: 247 patients had one LRR (94 two and 39 three). Mean OS was 10.1 years. Number of LRR was not correlated with OS. Positive HR status was significantly correlated with longer OS. Patients, who changed from primarily ER negative to positive at first LRR had a significantly longer OS compared to those, who remained or changed to ER negative (p < 0.01). Tumor size and grading correlated inversely with OS (both: p < 0.001). BCS at first LRR correlated with a significantly better OS than mastectomy (p < 0.001). LRR cases with chemotherapy had a shorter OS. Irradiation and/or endocrine therapy after LRR were not correlated with OS. Conclusions: Patients with positive HR status had the best survival data. HR should always be determined. In positive cases, endocrine therapy is recommended. As clinical data are good, BCS at first LRR can be suggested for more patients.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Breast cancer; Breast conserving surgery; Locoregional recurrence; Predictive factor; Relapse